2009
DOI: 10.1175/2009jcli2864.1
|View full text |Cite
|
Sign up to set email alerts
|

The Extreme Cold Anomaly over Southeast Asia in February 2008: Roles of ISO and ENSO*

Abstract: A record-breaking, long-persisting extreme cold anomaly (ECA) over Southeast Asia, accompanied by an intraseasonal convection over the Maritime Continent, is identified during the La Niñ a mature phase in February 2008. The cause of the ECA, in particular the role of the intraseasonal oscillation (ISO) and El Niñ o-Southern Oscillation (ENSO) on the ECA, is investigated by diagnosing observations and conducting numerical experiments.The ECA is associated with an enhanced prolonged Siberian high (SH) and a pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Jones et al (2011) demonstrated a relationship between the MJO and extreme precipitation over the United States and Hong and Li (2009) investigated the extreme cold anomaly over Southeast Asia in February 2008. Jones et al (2011) demonstrated a relationship between the MJO and extreme precipitation over the United States and Hong and Li (2009) investigated the extreme cold anomaly over Southeast Asia in February 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al (2011) demonstrated a relationship between the MJO and extreme precipitation over the United States and Hong and Li (2009) investigated the extreme cold anomaly over Southeast Asia in February 2008. Jones et al (2011) demonstrated a relationship between the MJO and extreme precipitation over the United States and Hong and Li (2009) investigated the extreme cold anomaly over Southeast Asia in February 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Also not clear is why these abnormal activities were so stable for so long. Suggestions as to the roles of La Niña, the north polar vortex, and intraseasonal oscillation have been made but definitive answers have not been found (Hong and Li 2009;Gao 2009).…”
mentioning
confidence: 99%
“…Although the extratropical factors are thought to be the main cause of this disaster (e.g. Wen et al, 2009;Zhou et al, 2009;Han et al, 2011), an MJO which originated from the western Indian Ocean around mid-January also played a crucial role in the maintenance of the icy weather (Hong and Li, 2009). In this study, we will show that the initiation of this MJO case was preceded by a cold surge from West Asia.…”
Section: Introductionmentioning
confidence: 65%
“…A 200-day Lanczos low-pass filter was then applied to retain both the intraseasonal signals associated with the MJO and the synoptic features that may be important for the MJO initiation. it induced anomalous northerlies and contributed to the record-breaking cold anomaly and icy weather over southern China (Hong and Li, 2009). In the following, we will focus on the second MJO case and explore when and how it was initiated.…”
Section: Methodsmentioning
confidence: 99%